2018
DOI: 10.1021/acs.jpclett.8b01040
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for cis Amide Bonds in Peptoid Nanosheets

Abstract: Peptoid nanosheets are supramolecular protein-mimetic materials that form from amphiphilic polypeptoids with aromatic and ionic side chains. Nanosheets have been studied at the nanometer scale, but the molecular structure has been difficult to probe. We report the use of C-C dipolar recoupling solid-state NMR measurements to reveal the configuration of backbone amide bonds selected by C isotopic labeling of adjacent α-carbons. Measurements on the same molecules in the amorphous state and in nanosheets revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Peptoids can also adopt extended strands when the backbone alternates chirality between pro‐ S and pro‐ R backbones. Such a pattern creates a net‐linear strand with residues displayed above and below the backbone, similar to β‐sheets in proteins (Figure ) . However, unlike β‐sheets, the strands within a peptoid sheet are held together predominantly through the interactions of sidechains, as hydrogen bonding between backbones is not possible in peptoids …”
Section: Assigning Peptoid Specific Regions To the Ramachandran Plotmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptoids can also adopt extended strands when the backbone alternates chirality between pro‐ S and pro‐ R backbones. Such a pattern creates a net‐linear strand with residues displayed above and below the backbone, similar to β‐sheets in proteins (Figure ) . However, unlike β‐sheets, the strands within a peptoid sheet are held together predominantly through the interactions of sidechains, as hydrogen bonding between backbones is not possible in peptoids …”
Section: Assigning Peptoid Specific Regions To the Ramachandran Plotmentioning
confidence: 99%
“…Additionally, the lack of C α pendant groups allows peptoids to access conformers without a chiral preference. For example, peptoid strands, which give rise to many peptoid nanostructures, are composed of residues in alternating mirror‐image backbone conformations . N ‐alkylation of the polyglycine backbone expands the conformational space accessible to peptoids, as tertiary amides can typically adopt both cis ‐ and trans ‐amide rotamers (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the linear and untwisted peptoid backbone resulted from the ability of adjacent backbone monomers to adopt two opposed rotational states. A refined model of the nanosheets was recently developed in combination with solid‐state NMR dipolar recoupling measurements . B28 peptoids were synthesized incorporating 13 C isotopic labels on specific adjacent α‐carbons to study their distances and consequently the isomerization state of B28 backbone amide bonds (Figure C) .…”
Section: Bidimensional Nanostructuresmentioning
confidence: 99%
“…A refined model of the nanosheets was recently developed in combination with solid‐state NMR dipolar recoupling measurements . B28 peptoids were synthesized incorporating 13 C isotopic labels on specific adjacent α‐carbons to study their distances and consequently the isomerization state of B28 backbone amide bonds (Figure C) . PITHIRDS‐CT dipolar recoupling solid‐state NMR revealed that, in the center of the positively charged block of the B28, the backbone amide bonds were predominantly in cis configuration (Figure D).…”
Section: Bidimensional Nanostructuresmentioning
confidence: 99%
“…Peptoid nanosheets are a functionally diverse class of materials that show great promise as affinity reagents, templates for mineralization, and as cell‐surface mimetics. Nanosheets have a well‐defined molecular structure with their backbones containing primarily cis amide bonds, as determined by solid‐state NMR, X‐ray diffraction, electron microscopy and atomic force microscopy, despite being comprised of only these three sterically unhindered monomers. However, because the nanosheets are micron‐scale objects (in length and width) and tumble very slowly in solution, their detailed molecular conformations cannot be probed by solution NMR, which is very often the technique of choice for studying molecular structure and dynamics in solution.…”
Section: Introductionmentioning
confidence: 99%